2005
DOI: 10.1086/430435
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Hydrogen Formation on Ice Under Interstellar Conditions

Abstract: The results of experiments on the formation of molecular hydrogen on low density and high density amorphous ice surfaces are analyzed using a rate equation model. The activation energy barriers for the relevant diffusion and desorption processes are obtained. The more porous morphology of the low density ice gives rise to a broader spectrum of energy barriers compared to the high density ice. Inserting these parameters into the rate equation model under steady state conditions we evaluate the production rate o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(161 citation statements)
references
References 38 publications
6
152
3
Order By: Relevance
“…The recombination reaction of hydrogen atoms, forming molecular hydrogen, is also taken into account. Since H 2 has a low binding energy with respect to water ice (Tielens & Allamandola 1987;Perets et al 2005), and since its reaction of formation releases chemical energy (Hollenbach & Salpeter 1970), we assumed that the H 2 molecules are desorbed in the gas phase as soon as they are formed. Finally, IR observations have shown that CO 2 may be a major component of ices with abundances reaching 30% with respect to to water in some cases (Dartois et al 1999;Pontoppidan et al 2008).…”
Section: Chemical Networkmentioning
confidence: 99%
“…The recombination reaction of hydrogen atoms, forming molecular hydrogen, is also taken into account. Since H 2 has a low binding energy with respect to water ice (Tielens & Allamandola 1987;Perets et al 2005), and since its reaction of formation releases chemical energy (Hollenbach & Salpeter 1970), we assumed that the H 2 molecules are desorbed in the gas phase as soon as they are formed. Finally, IR observations have shown that CO 2 may be a major component of ices with abundances reaching 30% with respect to to water in some cases (Dartois et al 1999;Pontoppidan et al 2008).…”
Section: Chemical Networkmentioning
confidence: 99%
“…Note that in the analysis of the experimental results, presented in Katz et al (1999) and Perets et al (2005), no distinction between H and D atoms was made to ensure that the number of fitting parameters was small. The possibility of the tunneling of adsorbed atoms between adsorption sites was studied by Cazaux & Tielens (2004).…”
Section: The Interaction Between Hydrogen/deuterium Atoms and Dust Grmentioning
confidence: 99%
“…These parameters are based on a series of experiments and subsequent analysis, reported in Katz et al (1999), Perets et al (2005) and Perets et al (2007). The attempt rate ν I is often assumed to be equal to 10 12 s −1 .…”
Section: The Interaction Between Hydrogen/deuterium Atoms and Dust Grmentioning
confidence: 99%
“…In recent years, we have conducted a series of experiments on the formation of molecular hydrogen on dust grain analogs such as polycrystalline silicates (Pirronello et al 1997a(Pirronello et al , 1997b, amorphous carbon , and amorphous water ice (Manico et al 2001;Roser et al 2002Roser et al , 2003Perets et al 2005), under astrophysically relevant conditions. In these experiments, the surface was irradiated by beams of H and D atoms.…”
Section: Introductionmentioning
confidence: 99%